Cultural Intelligence and Intellectual Capital: Evidence from External Audit Firms - Sohail Momeny; Zahra Poorzamani (Iranian Journal of Accounting, Auditing & Finance)
Intellectual capital (IC) is acknowledged as a strategic advantage for improved performance, and cultural intelligence (CI) is becoming a more significant asset for managers, employees, entrepreneurs, and their organizations. This paper aims to present a new framework for managing IC within audit firms, considering the perspective of CI. The method of the present study is a descriptive survey in terms of data collection and applied from the standpoint of purpose. The statistical population of this study includes all auditors working in audit firms under the membership of the Society of Certified Public Accountants, and 319 individuals made up the statistical sample. The partial least squares approach was used to conduct structural equation modeling, which examined the impact of research variables on IC and fitted the suggested model. According to the study's findings, CI has a positive and significant relationship with the human, structural, and relational elements of IC and auditors will have more human capital (HC), structural capital (SC), and relational capital (RC) as IC rises. The research is exploratory and the framework offers opportunities for refinement. Future studies are required to confirm the framework's applicability to other organizations intended to serve as CI systems. Contribution to the IC research literature is highlighted, expanding the concept of IC value creation beyond the audit firms into wider society and developing a new perspective for managing IC in the audit firms adopting the CI approach. The framework can be used to manage IC strategically in all the systems interpreted as CI systems in which the role of IC creation from multiple actors is relevant. This makes comprehending how IC helps the region and society where the audit firms operate possible. This study is paramount since limited empirical evidence exists, particularly in developing/underdeveloped countries worldwide. The paper's originality lies in combining topics typically covered by literature in different fields, such as IC management and CI perspective. The CI approach provides a novel contribution to managing IC and is intended to inspire future research.